The PSI handbook of virtual environments for training and education developments for the military and beyond - Schmorrow, Dylan; Cohn, Joseph; Nicholson, Denise (Technology, psychology, and health, 2009)
The increasingly complex environment of the 21st century demands unprecedented knowledge, skills and abilities for people from all walks of life. One powerful solution that blends the science of learning with the technological advances of computing is Virtual Environments. In the United States alone, the Department of Defense has invested billions of dollars over the past decade to make this field and its developments as effective as possible. This 3-volume work provides, for the first time, comprehensive coverage of the many different domains that must be integrated for Virtual Environments to fully provide effective training and education. The first volume is dedicated to a thorough understanding of learning theory, requirements definition and performance measurement, providing insight into the human-centric specifications the VE must satisfy to succeed. Volume II provides the latest information on VE component technologies, and Volume III offers discussion of an extensive collection of integrated systems presented as VE use-cases, and results of effectiveness evaluation studies. The text includes emerging directions of this evolving technology, from cognitive rehabilitation to the next generation of museum exhibitions. Finally, the handbook offers a glimpse into the future with this fascinating technology. This groundbreaking set will interest students, scholars and researchers in the fields of military science, technology, computer science, business, law enforcement, cognitive psychology, education and health. Topics addressed include guidance and interventions using VE as a teaching tool, what to look for in terms of human-centered systems and components, and current training uses in the Navy, Army, Air Force and Marines. Game-based and long distance training are explained, as are particular challenges such as the emergence of VE sickness. Chapters also highlight the combination of VE and cybernetics, robotics and artificial intelligence.